2012
DOI: 10.1016/j.lfs.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

ET-1 from endothelial cells is required for complete angiotensin II-induced cardiac fibrosis and hypertrophy

Abstract: This study underscores the significance of ET-1 from the vasculature in the process of AngII-induced cardiac hypertrophy and fibrosis, independently from blood pressure. Endothelial ET-1 represents therefore a possible pharmacological target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 43 publications
1
43
0
2
Order By: Relevance
“…Adiarto et al have reported that vascular endothelium derived ET-1 is essential for Ang II induced cardiac hypertrophy and fibrosis in mice [10]. Combining our previous report that MRTF-A mediates hypoxia-induced ET-1 production in endothelial cells and our observation that Ang II activates MRTF-A in endothelial cells (Fig.…”
Section: Mrtf-a Contributes To Ang II Induced Et-1 Transactivation Insupporting
confidence: 85%
See 1 more Smart Citation
“…Adiarto et al have reported that vascular endothelium derived ET-1 is essential for Ang II induced cardiac hypertrophy and fibrosis in mice [10]. Combining our previous report that MRTF-A mediates hypoxia-induced ET-1 production in endothelial cells and our observation that Ang II activates MRTF-A in endothelial cells (Fig.…”
Section: Mrtf-a Contributes To Ang II Induced Et-1 Transactivation Insupporting
confidence: 85%
“…Recently, it has been reported that vascular endothelium derived ET-1 is essential for Ang II induced cardiac hypertrophy and fibrosis in mice [10]. Previously we have demonstrated that myocardin related transcription factor A (MRTF-A) is activated by oxidized LDL (oxLDL) in vascular endothelial cells and contributes to endothelial disorder [11].…”
Section: Introductionmentioning
confidence: 99%
“…ET-1 expression can be up-regulated by Ang II in vascular endothelial cells [7]. In contrast, endothelial-specific ablation of ET-1 abrogates Ang II-induced pathological hypertrophy in mice [8].…”
Section: Introductionmentioning
confidence: 99%
“…55 The development of cardiac fibrosis and hypertrophy in response to Ang II is impaired in mice with vascular endothelial cell-specific ET-1 deficiency. 56 These results are consistent with observations that Ang-II induces ET-1 via extracellular signal-regulated kinase and reactive oxygen species and the serum-responsive transcription factor myocardin-related transcription factor (MRTF) A. [57][58][59] MRTF-A is recruited to the ET-1 promoter by c-Jun/c-Fos (activator protein 1) in response to Ang-II treatment; moreover, MRTF-A deficiency improved Ang-II-induced cardiac hypertrophy and fibrosis in mice.…”
Section: Endothelin-1mentioning
confidence: 99%